Aggression and Emotional Intelligence among College Students of Rural and Urban Area - Manjeet (Innovative Research Thoughts, 2017)
The study was conducted on 30 students of rural area and 30 of urban area were randomly selected from various college students of Haryana. The criterion measure chosen to test the hypothesis in this study was aggression inventory by M. K. Sultania (2006) and emotional intelligence scale by Dr. S. K. Mangal and Dr. Shubhra Mangal (2004). The data was collected through direct contact with the respondents. The findings revealed that there is no significant difference between Aggression level among rural and urban area students, the calculated „t‟ ratio was 0.148. There is significant difference between Emotional Intelligence among rural and urban area students, the calculated „t‟ ratio was 1.269.